Report on Training of Enumerators on Baseline Household Survey of Mixed Farming Systems in Bangladesh - Haque, Abdul; Ahmed, Sharif; Bhandari, Humnath (International Rice Research Institute, 2024)
The International Rice Research Institute (IRRI) implemented a baseline household (HH) survey under the CGIAR initiative on Mixed Farming Systems (MFS) (https://www.cgiar.org/initiative/mixed-farming-systems/) in Bangladesh. The basic objective of the survey is to understand the Initiative's effect on beneficiary farmers’ livelihoods and help identify successful agricultural technologies and practices. The results from the survey will be used to determine and understand major constraints and opportunities for improving farmers’ livelihoods. The survey data will be collected through digital data collection software called Survey Solution (https://mysurvey.solutions/en/) designed by the World Bank. For conducting the HH survey IRRI has hired the AVA Department Society (AVADS) as the Service Provider (SP) to complete the whole HH survey at the preselected villages in Bangladesh. The SP will do the HH survey with four teams, each containing four enumerators and a team leader. IRRI has organized a training event for the HH survey enumerators so that they can carry out their respective tasks efficiently. The training agenda is presented in Annex 1. This report reflects the training activities provided to the HH survey enumerators from 23 to 26 September 2024 by the International Rice Research Institute (IRRI) in collaboration with the AVA Development Society (AVADS) at Rangpur, Bangladesh.